2022
DOI: 10.3389/fphar.2021.759741
|View full text |Cite
|
Sign up to set email alerts
|

The Gene Expression Analysis of Peripheral Blood Monocytes From Psoriasis Vulgaris Patients With Different Traditional Chinese Medicine Syndromes

Abstract: Psoriasis is chronic skin disease and an important health concern. Traditional Chinese Medicine (TCM) has shown great promise in the treatment of psoriasis. However, the correlation between TCM Syndromes and genomics of psoriasis has not been evaluated. Here, we analyzed gene expression profiling of monocytes from psoriasis vulgaris patients with different TCM syndrome types to reveal the molecular basis of different psoriasis syndromes. Of the 62 cases of psoriasis vulgaris recruited, 16, 23, and 23 cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…Moreover, previous evidence has shown that polymorphisms in the FTO gene can affect the severity of psoriasis ( Merola et al, 2022 ). Meanwhile, compared to healthy controls, the mRNA level of IGF2BP3 in psoriasis lesions was upregulated ( Xing et al, 2022 ), and the level of HNRNPA2B1 was significantly downregulated ( Lu et al, 2021 ). Our experiments verified that the mRNA level of YTHDC2 was elevated in psoriasis patients, and the expression of METTL3 and IGF2BP2 was significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous evidence has shown that polymorphisms in the FTO gene can affect the severity of psoriasis ( Merola et al, 2022 ). Meanwhile, compared to healthy controls, the mRNA level of IGF2BP3 in psoriasis lesions was upregulated ( Xing et al, 2022 ), and the level of HNRNPA2B1 was significantly downregulated ( Lu et al, 2021 ). Our experiments verified that the mRNA level of YTHDC2 was elevated in psoriasis patients, and the expression of METTL3 and IGF2BP2 was significantly decreased.…”
Section: Discussionmentioning
confidence: 99%